Antigenicity modulation upon peptide cyclization: application to the GH loop of foot-and-mouth disease virus strain C-1-Barcelona - Gomes, P (2001)
Foot-and-mouth disease virus (FMDV) isolate C-1-Barcelona (or C-S30) includes four replacements within its immunodominant site (GH loop, residues 136-150 of capsid protein VP1, YTTSTRGDLAHVTAT), relative to reference strain C-S8cl (YTASAR-GDLAHLTTT). Although one of the mutations in C-S30 ((147)Leu --> Val) is known to be detrimental for antibody recognition, reactivity of this isolate with the neutralizing monoclonal antibody (mAb) 4C4, raised against FMDV C-1-Brescia (GH loop: YTASTRGDLAHLTAT), was indistinguishable from those of strains C-S8cl or C-1-Brescia. A structural interpretation for these somewhat striking findings is available, based on the observation that 15-residue peptides reproducing the C-S30 and C-S8cl GH loops adopt very similar, quasi-circular, conformations in crystal complexes with 4C4. Nevertheless, surface plasmon resonance (SPR) kinetic analyses of the interactions between these peptides and three anti-GH loop mAbs have now revealed that the linear C-S30 peptides were less antigenic in solution than their C-S8cl and C-1-Brescia counterparts. We have, therefore, tried to modulate peptide antigenicity in solution by cyclization. Functional SPR and structural two dimensional proton nuclear magnetic resonance (2D-H-1 NMR) studies of both linear and cyclic peptide antigens are discussed here. Conformation seems to have an important role in peptide antigenicity, even when continuous (i.e. linear) antigenic sites are involved.